Exploration of pitcher plants in University of Palangka Raya - Muhammad Rizki; Vinsen Willi Wardhana Wardhana; Mawardin Mawardin; Siti Sunariyati (Universitas Muhammadiyah Prof. Dr. Hamka, 2021)
Background: This study is a pilot project on the effectiveness of flora, especially the type of semar bag (Nepenthes sp) found at the University of Palangka Raya (UPR). The research aims to identify semar bag plants at the University of Palangka Raya. The initial observations found at least more than one type of semar bag that lives in the peat forest of the UPR campus. The study was conducted in August-November 2020. Methods: Semar bag diversity data is collected by cruising methods. The data was analyzed using literature studies to be further identified using a sealed bag identification manual. Results: The study found three species of semar bags found in the forest campus of Palangka Raya University. The bag is a type of Nepenthes mirabilis (Lour.) Druce, Nepenthes gracilis Korth., and Nepenthes rafflesiana Jack. Morphological characters that distinguish these three species are the morphology of leaves and pouches. The range of environmental parameter values is air temperature 28-38oC, medium-open coverage, humidity 62-98%, and soil pH 5-7.5. Conclusions: This study's results are expected to be a database of flora biodiversity in Central Kalimantan.